2010
DOI: 10.1093/annonc/mdp401
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of weekly paclitaxel combined with carboplatin versus standard paclitaxel combined with carboplatin for elderly patients with advanced non-small-cell lung cancer

Abstract: Background:The optimal platinum doublet regimen in elderly patients with non-small-cell lung cancer (NSCLC) is still uncertain. We conducted a randomized phase II study to compare the efficacy and safety of weekly paclitaxel combined with carboplatin with those of the standard schedule. Results: Eighty-two patients were enrolled. The ORR and median progression-free survival were 55% and 6.0 months for the weekly arm and 53% and 5.6 months for the standard arm. Grade 3/4 neutropenia and peripheral neuropathy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…These findings incorporated with the results of Suresh et al 28 and Sakakibara et al 29 Although the differences in the duration of treatment cycle between the two arms (4 and 3 weeks, respectively, for arms 1 and 2) could have contributed to differences in median TTP, the overall survival and 1-year survival results are comparable between the two arms. The lower incidence of grade 2/3 neuropathy was achieved with the weekly paclitaxel regimen despite the same doseintensity of paclitaxel on both the arms.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These findings incorporated with the results of Suresh et al 28 and Sakakibara et al 29 Although the differences in the duration of treatment cycle between the two arms (4 and 3 weeks, respectively, for arms 1 and 2) could have contributed to differences in median TTP, the overall survival and 1-year survival results are comparable between the two arms. The lower incidence of grade 2/3 neuropathy was achieved with the weekly paclitaxel regimen despite the same doseintensity of paclitaxel on both the arms.…”
Section: Discussionsupporting
confidence: 76%
“…Our results are slightly higher than some study as our regimen used as first-line treatment in previously untreated patients and the median age was slightly lower than in those studies. However, recent randomized phase II trial comparing weekly paclitaxel combined with carboplatin with standard paclitaxel combined with carboplatin in elderly patients (≥ 70 years) with advanced NSCLC reported high overall response rate 55% and 53%, respectively 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly NSCLC patients, the combination of carboplatin and weekly paclitaxel was associated with survival benefits as compared with single-agent chemotherapy [28]. Some weekly combination regimens were preferable for elderly patients or those with severe comorbidity [29][30][31]. Pemetrexed was not selected since its safety for ESRD patients receiving hemodialysis has yet to be confirmed, while gefitinib was not selected due to the EGFR genotype of the lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, three phase 2 trials, and a subset analysis restricted to elderly patients from a phase 3 trial, also showed that weekly paclitaxel plus monthly carboplatin chemotherapy could be administered safely to elderly patients with promising OS results [109][110][111][112]. Indeed, in all these trials, involving a total of 206 patients over the age of 70 yrs, 1-yr survival ranged from 31% to 62%.…”
Section: Elderly Patients Deserve Active Treatmentmentioning
confidence: 96%